THE ROLE OF SECONDARY EDUCATION SCHOOLS AND VOCATIONAL TRAINING INSTITUTIONS IN STUDENTS’ PROFESSIONAL SELF-DETERMINATION: THE CURRENT SITUATION AND MAIN PROBLEMS - Antanaitienė, Aistė; Sajienė, Laima (Acta Paedagogica Vilnensia, 2012)
Vocational choice as one of the key goals in personal career development requires a new approach. The essence of this approach is focusing on the objective and subjective factors that influence professional self-determination. These concepts being the basis of professional self-determination, educational institutions play an important role in human development. The first step of professional self-determination takes place in secondary schools, but equally important is the role of initial training institutions. The aim of the research was to identify the current situation and problems of career education in secondary schools and vocational training institutions as an essential factor of vocational self-determination. The research methodology: scholastic literature analysis, questionnaire-based survey, statistical analysis of survey results. The research included 584 general education students from middle school and high school forms as well as 616 pupils from initial vocational training institutions. The distribution of the respondents by the type of educational institution is proportional. Results. More attention to the problems of professional self-determination is paid in general education schools than in vocational training institutions, as the factor analysis has shown that in secondary schools students are more often than in vocational training schools advised by a specialist (58.2% of secondary school students agree compared to 41.4% of students from vocational training schools, χ2 = 40,914, p < 0.05); however, vocational training institutions students are more likely to be advised by a class tutor or deputy director (43.3% of secondary school students agree as compared to 57.3% of vocational training school students, χ2 = 15.85, p < 0.05). Conclusions: • The role of career information points in schools is not significant, because most students do not know about them and have no information about their services. • The activity of career information points is still often limited to the organization of events and dissemination of information about occupations, but little attention is given to individual work with students in setting their professional direction and highlighting the further career opportunities. • Students are advised and informed about career opportunities most often by teachers, form tutors, visiting professional advisors. • The efforts of school psychologists, social workers and professional advisors in the process of career education is insufficient.